Censurae Librorum - Pierzak, Damian (Polskie Towarzystwo Filologiczne, 2021)
Tobias Boll, Ciceros Rede cum senatui gratias egit. Ein Kommentar, Berlin–Boston: Walter de Gruyter, 2019 (Göttinger Forum für Altertumswissenschaft. Beihefte, Neue Folge 10), 260 pp., ISBN 978-3-11-062921-7, €113.95.